Analysis of Factors Influencing the Implementation of Sustainable Project Management (SPM) in the Construction Industry in Indonesia - Farhan, Ariq; Rachmawati, Titi Sari Nurul (CSID Journal of Infrastructure Development, 2026)
The construction industry contributes significantly to economic growth but also carries substantial environmental and social costs. Construction activities generate carbon emissions, consume natural resources, and produce large volumes of waste. Despite growing theoretical development of Sustainable Project Management (SPM) frameworks, empirical evidence on the actual level of SPM implementation in Indonesia's construction sector remains limited. This study aims to identify the factors that influence SPM implementation and measure the level of implementation as perceived by construction professionals. A quantitative survey was administered to 99 professionals across infrastructure, building, and industrial construction sectors in Indonesia. Data were collected through a Likert-scale questionnaire and analysed with descriptive statistics. Implementation was assessed against the P5 Framework (People, Planet, Prosperity, Process, Product). All seven factors in this study, including leadership, awareness, HR competence, organisational support, regulation, stakeholder engagement, and organisational culture, scored in the high category (mean range: 3.68–3.89). All five P5 dimensions also achieved high mean scores. Product (3.941) and People (3.917) were the leading dimensions. These findings indicate that Indonesian construction professionals perceive SPM implementation as consistently high across organisational and external dimensions. This study contributes empirical data to the SPM literature in the Indonesian context and provides a baseline for monitoring future implementation progress. The results identify HR competence (3.681) as the priority area for technical training investment, with direct implications for industry development programs and construction education curricula.